IS TEACHERS’ EMOTIONAL INTELLIGENCE INDEPENDENT OF THEIR GENDER AND TEACHING EXPERIENCE? A CASE BASED STUDY - Das, Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present world is changing faster than ever before.People are hence facing unparalleled challenges in their lives.Nowadays,teachers at all levels are expected to perform multiple roles with efficacy; thereby management of emotions is very important.Managing emotion depends on one’s emotional intelligence. The present study investigated whether Higher Secondary school teachers’ emotional intelligence is independent or dependent ontheir gender and teaching experience. The study communicated thatthe Higher Secondary school teachers’emotional intelligence is independent of their gender and teaching experience.